The Bahá'í Faith in the Kurdistan Region Roots and the experience of coexistence - Hassan Khaled Mustafa Al-Mufti; Kaban Abdul Karim Ali (Zanco Journal of Humanity Sciences)
The roots of the Baha’i religion go back to the efforts of Ali Muhammad, known as “The Bab” in Iran and Iraq, and he was the first to prepare the ground among the Shiite Muslims for the emergence of the awaited Messenger, who is (Mirza Husayn Ali), who was later known as (Baha’Allah), one of the followers of the Bab, who His order was Sufi in the beginning, and he settled for a period in Iraqi Kurdistan, specifically in the Sarklu area in Sulaymaniyah, then returned to Baghdad and announced his new vocation there in the year 1863, then he was exiled to Istanbul and Edirne, until he settled in the city of Acre in Palestine, where he died in 1892 AD.     The Baha'i faith spread in Iran, Iraq and some other countries. Baha'is believe that all major religions are from the same source (God), and God Almighty created all human beings equal. Therefore, they believe in human unity and that humanity is in great need of understanding the nature and purpose of life. This is to establish A unified vision towards the future of human society, and they believe that Bahá'u'lláh's writings and blogs, which are contrary to the true Islamic religion in terms of substance and vision, help them to understand and adopt this vision.  This research - in addition to the introduction and conclusion - consists of four sections: the first section deals with an introduction to the Baha'i religion and the date of its emergence, while the second topic is devoted to the study of the Baha'i faith, in order to identify its most prominent ideological features  , and the third topic deals with Kurdistan and the Baha'i religion, explaining The position of Kurdistan in the spiritual formation of Bahá'u'lláh and among adherents of the religion in general. The fourth and final section dealt with the experience of coexistence of the followers of religion in the Kurdistan region, showing its past and present reality, and the study concluded by presenting the most important results of the study.